New approach for estimate parameters of machine asynchronous, ISSN / e-ISSN 2320–3331 / 2278-1676 - Bouhantala Abdelmalik; Benbouza Mohamed Salah (IOSR Journal of Electrical and Electronics Engineering, 2014)
Rotating electrical machines play an important role in the industrial world. Among them, the three- phase squirrel cage asynchronous machines are frequently used because of their robustness, their relatively simple construction and their low cost. Nevertheless, during their lifespan, these machines are submitted to external and internal stresses which can lead to several failures. In this paper, we present the estimate of the parameters sensitive to the defects, namely the rotor currents and resistances of the rotor bars, by using the Extended Kalman filter.